Evidence-Based Complementary and Alternative Medicine in Inpatient Care: Take a Look at Europe. (April 2015) - Romeyke, Tobias; Stummer, Harald
The aim of this report is to provide the reader an overview of the complex therapy currently used within the German health system. Complex therapies in inpatient care in Germany establish the basis for an integrative and interdisciplinary provision of services. They define minimal criteria for the organization of a hospital, enable the integration of different therapeutic approaches, and therefore, lead to an intensive and holistic treatment by a specially trained team. The German model can be viewed as a pilot program for the introduction of integrative patient-centered care in other hospitals around the world.